Genetski vidik naravne obnove smrekovega sestoja na nastali raziskovalni ploskvi Šijec na Pokljuki - Božič, Gregor (Zbornik gozdarstva in lesarstva, 2005)
The aim of the research was to check the ability of natural regeneration for sustainable conservation of Picea abies (L.) Karst. genetic resource in the permanent forest research plot Šijec on the Pokljuka plateau, Slovenia. The genetic structures of spruce stand and its natural regeneration centres of different size have been studied by means of electrophoretic analysis of ten enzyme systems (GDH, F-EST, GOT, IDH, LAP, MDH, PGI, PGM, SKDH, 6-PGDH) for 15polymorphic isozyme gene loci. Under certain conditions, the genetic structures of 64 adult mother trees of the basic stand compared to 101 young spruce trees from the regeneration centres included in the study were closely similar. The regeneration of spruce stand by natural regeneration permanently conserves the spruce genetic resource and is, in the case of bigger regeneration centres, also an assurance of its continuous adaptability.
Keywords: genetske raziskave; ohranjanje gozdov; Picea abies; Pokljuka; pomlajevanje